Cesarean section in a patient with sickle cell disease, mitral stenosis, pulmonary arterial hypertension, and thrombocytosis - Hansda, Upendra; Mohanty, Chitta Ranjan; Sahoo, Sangeeta (Indian Journal of Case Reports, 2018)
-